Archaeology as cultural history - Morris, Ian, 1960- (Malden, Mass ; Oxford)
xiv, 358 sayfa
Keywords: “This book shows the reader how much archaeologists can learn from recent developments in cultural history. Cultural historians deal with many of the same issues as postprocessual archaeologists, but have developed much more sophisticated methods for thinking about change through time and the textuality of all forms of evidence. The author uses the particular case of Iron Age Greece (c. 1100-300 BC) to argue that text-aided archaeology, far from being merely a testing ground for prehistorians’ models, is in fact in the best position to develop sophisticated models of the interpretation of material culture.” --